Individualização da pena e violência simbólica - Schneider, Ingrid (2013)
This research has been focused on the individualization of punishment, understanding it as a symbolic exercise of violence coming from the legal field, staring from approaching penal theories produced by the Penal Dogmatic, which are, in fact, theories that aim to provide legitimacy to the state monopoly when punishing. The individualization of punishment, tributary from retributive and prevention theories, has taken place in the Brazilian criminal ordering as a fundamental right with constitutional entry. Although its basis has been saving the principle of penal proportionality, it has also constituted one more dispositive for the movement of penal rationalization, fixed on a complex quantification system, apparently turned to humanization. The solution found by the Brazilian legal and criminal ordering for the individualization of punishment, strongly deliberating the circumstances that not only meet the author s individual characteristics, but also tends to direct sentences in the pathway of Criminal Law by him, has maintained present, this way, the etiological pattern of legal and criminal positivism. Thereby, the analysis of a sample of first degree condemnation sentences on theft or simple stealing and drug traffic crimes practiced in Porto Alegre, selected from criminal appeals addressed to TJRS in 2009 and 2010, aim to demonstrate the hypothesis that, beyond reproducing law terms literally without justifying them, has indicated that criminal dosimetry was permeated by notions of common sense, what currently has signified a strong punitive tendency. It is not possible, however, to affirm that individualization criteria have been applied in most of the sentences. Therefore, they have specially predominated on stealing and traffic cases, onerous punishments, and being executed in closed regime, regardless of dealing with criminality mostly unarmed, non-organized, disperse and with agents and victims from popular extraction, characterizing, thus, the selectivity of the criminal system. Such symbolic exercise of violence has been understood once it means imposing submission and exclusion, as if it were the scientific application of canonic texts - as revealing the strong presence of anti-guaranteed tendencies in the magistracy of the first degree.